The importance of interactivity for elderly with dementias through information technologies (Research, Society and Development, 2020)
This work is an extension project that arose from the importance of the care developed for elderly people with dementia and emerged from the growing concerns with health strategies and actions through information technologies. It aims to describe the interactivity of an information and communication technology about the elderly with dementia. It is a qualitative, descriptive, experience report type study of the extension project developed at the School of Nursing through the Dean of Extension of Federal Fluminense University. This interactive technology provides the dissemination and relevant discussions on guidelines on the need to support family and caregivers of elderly people with dementias, promoting relevant research that results in benefits to this clientele. This technology as an educational tool allows to establish the exchange of knowledge, in an interactive, effective and fast way, considering the family member/caregiver as active in this care process through continuous planning.